2017
DOI: 10.1016/j.wear.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Mn concentration on the tribocorrosion resistance of Al–Mn alloys

Abstract: An increase in the complexity and severity of service conditions demands improvements in the design of new engineering materials that are resistant to the effects of tribocorrosion. Unfortunately, there is typically a tradeoff between wear and corrosion resistance, even for important passive metals such as Al alloys. In this work, it was shown that alloying Al with Mn in supersaturated solid solution simultaneously increased the wear resistance of the Al as well as the protectiveness of the passive layer, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…The cathodic and anodic reaction can be presented as follows: When Monel 400 alloy slides against the Al2O3 pin in seawater, the alloy will suffer serious tribo-corrosion, resulting in material loss. Generally, electrochemical corrosion and mechanical wear interact in a synergistic way; that is, corrosion will promote wear, and wear, in turn, will promote corrosion [39][40][41]. However, in this paper, the corrosion of the alloy significantly inhibits its wear, that is, ΔWc < 0, resulting in significantly greater material loss and frictional coefficient after mechanical wear tests than that after tribocorrosion tests (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 68%
“…The cathodic and anodic reaction can be presented as follows: When Monel 400 alloy slides against the Al2O3 pin in seawater, the alloy will suffer serious tribo-corrosion, resulting in material loss. Generally, electrochemical corrosion and mechanical wear interact in a synergistic way; that is, corrosion will promote wear, and wear, in turn, will promote corrosion [39][40][41]. However, in this paper, the corrosion of the alloy significantly inhibits its wear, that is, ΔWc < 0, resulting in significantly greater material loss and frictional coefficient after mechanical wear tests than that after tribocorrosion tests (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 68%
“…It can be seen that for passive alloys such as Al, the mechanical disruption during tribocorrosion leads to local breakdown/removal of the passive film on the wear track and exposing a depassivated area which leads to a decrease in the corrosion potential by ~ 20 mV. Our earlier work 16 showed that the magnitude of corrosion potential reduction is strongly related to the microstructure of the metal given the testing parameters ( e.g., applied load, sliding speed, temperature) are the same. For Al with higher hardness and finer microstructure, the same applied load may lead to a smaller depassivated area, hence smaller change in corrosion potential.…”
Section: Discussionmentioning
confidence: 89%
“…However, current evolution during tribocorrosion test at imposed cathodic or anodic potentials can be monitored. An example can be found in our previous work 16 . Figure 12 shows the current evolution of Al thin film during tribocorrosion at an imposed anodic potential of 200 mV more positive than OCP.…”
Section: Discussionmentioning
confidence: 98%
“…EIS can measure the solution resistance (Rs), electric double layer capacitance (Cdl), charge transfer resistance (Rct), pore During a corrosion test, when the working electrode is at a fixed cathodic potential, corrosion is suppressed, whereas, at a fixed anodic potential, a passive film forms on the metallic surface. Thus, a potentiostatic (PS) test can be performed at fixed anodic potential to understand the structure and stability of the passive film by measuring the current, I = At −k , where A is a constant based on electrolyte and potential and k is the slope in the logarithmic I vs. logarithmic t graph indicating the passive film compactness factor [9].…”
Section: Corrosion Characterization Techniquesmentioning
confidence: 99%
“…However, halides and other anions can penetrate the passive films and initiate localized pitting or crevice corrosion [8]. Alloying metals can promote, strong and enduring passive film formation [9]. However, alloying changes the chemical composition and metal properties, which may not be cost effective or feasible for particular applications.…”
Section: Introductionmentioning
confidence: 99%